Study of the anatomical structure of the aboveground organs of Catalpa speciosa of the 1st year vegetation - Aitymov, A.K.; Yamburov, M.S. (Fundamental and Experimental Biology, 2023)
Woody-shrub vegetation has a key role in greening the urban environment. The excellent decorative qualities of the catalpa are important when choosing a woody plant for introduction in the conditions of the Karaganda region. Seedlings for a particular region must be grown locally to improve their adaptive properties. For a more complete study of the biological features of the species, an anatomical study of young catalpa plants was carried out. It was found that the leaf of the catalpa of the dorsal-ventral type, the stomata of the diacytic type, the cells of the epidermis with winding walls, trichomes and essential -oil glands are located on it; the petiole of the leaf is rounded in shape, with well-developed mechanical tissues around conductive bundles. On the internal structure of the stem and root, the beginning of the formation of cork tissue and the transition to a non-bundle type of structure of the conductive system is observed. In general, the structure of the catalpa is excellent evidence of the mesoxerophyte structure of the plant, which shows its demands on humidification conditions. Leaves are light type, that is, plants when planning green construction must be placed in areas with sufficient lighting. The results obtained will be supplemented by the study of anatomical indicators of plants of subsequent years of development.